The effects of letrozole and clomiphene citrate on ligands expression of Wnt3, Wnt7a, and Wnt8b in proliferative endometrium of women with Polycystic ovarian syndrome. (2nd September 2018) - Mehdinejadiani, Shayesteh; Amidi, Fardin; Mehdizadeh, Mehdi; Barati, Mahmood; Safdarian, Leili; Aflatoonian, Reza; Alyasin, Ashraf; Aghahosseini, Marzieh; Pazhohan, Azar; Hayat, Parisa; Mohammadzadeh kazorgah, Farzaneh; Sobhani, Aligholi
Abstract: Polycystic ovarian syndrome (PCOS) is a common endocrinologic disorder in women of reproductive age characterized by polycystic ovaries, oligo/anovulation, and hyperandrogenism. Not only anovulation but also endometrial dysfunction can reduce fertility in PCOS patients. Wnt pathway is responsible for endometrial proliferation which be strongly regulated by estradiol. To determine the effects of clomiphene citrate (CC) and letrozole, we measured the expression of some main ligands of Wnt/β-catenin signaling including Wnt7a, Wnt3, and Wnt8b in the endometrial samples taken from PCOS women on day 12 of the menses who received 100 mg CC or 5 mg letrozole as well as from women without treatment. Significantly, the mean estrogen and progesterone concentration were lower and higher, respectively, in letrozole than CC. The mean endometrial thickness (ET) was significantly greater in letrozole compared to CC. Assessment of the mRNA and protein expression of Wnt7a, Wnt3, and Wnt8b showed significantly lower expression in CC than the letrozole and control groups. Collectively, letrozole provided a better molecular response in the endometrium of PCOS patients during the proliferative phase, similar to natural cycles, compared to CC. CC decreased the ligands expression of Wnt3, Wnt7a, and Wnt8b, resulting in endometrial dysfunction.